Islamic Values Amplify Entrepreneurial Confidence Through Self-Efficacy: Nilai-Nilai Islam Memperkuat Kepercayaan Diri Wirausaha Melalui Efikasi Diri - Fitriya, Ana Lailatul; Putra, Riyan Sisiawan; Zuhdi, Ubaidillah; Fatimah, Nuzulul (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2024)
This study examines the impact of Islamic values on the entrepreneurial behavior of Muslim business owners within the Nahdliyyin Entrepreneurs Association (HPN), with self-efficacy serving as an intervening variable. Using a quantitative approach, the research employs structural equation modeling – partial least square (SEM-PLS) and purposive sampling. Data was gathered from 92 Muslim entrepreneurs who met the criteria, through an online questionnaire distributed via Google Forms. The analysis was conducted using SmartPLS4 software. The findings reveal that both Islamic values and self-efficacy significantly and positively influence the entrepreneurial behavior of Muslim entrepreneurs. However, self-efficacy does not mediate the relationship between Islamic values and entrepreneurial behavior. These results suggest that while Islamic values and self-efficacy individually contribute to entrepreneurial behavior, the mediating role of self-efficacy may require further investigation. The study highlights the importance of fostering Islamic values and personal confidence to enhance entrepreneurial success.